2009
DOI: 10.1037/a0016869
|View full text |Cite
|
Sign up to set email alerts
|

Clinical assessment of affective instability: Comparing EMA indices, questionnaire reports, and retrospective recall.

Abstract: Traditional self-report measures of psychopathology may be influenced by a variety of recall biases. Ecological momentary assessment (EMA) reduces these biases by assessing individuals' experiences as they occur in their natural environments. This study examines the discrepancy between trait questionnaire, retrospective report, and EMA measures of affective instability in psychiatric outpatients either with a borderline personality diagnosis (BPD; n=58) or with a current major depressive episode or dysthymia (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
260
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 316 publications
(271 citation statements)
references
References 46 publications
8
260
1
2
Order By: Relevance
“…That BPD patients suffer from dramatic ups and downs in affect has always been clinical experience, but only recently have empirical studies verified the ups and downs in BPD by tracking affective states over time in daily life Links et al, 2007;. At the same time, research has shown that the relationship between questionnaire trait measures of affective instability and affective instability, as experienced in everyday life, is modest at best (Links, Heisel, & Garland, 2003;Solhan, Trull, Jahng, & Wood, 2009). The study by Solhan et al even showed that BPD patients do not remember their most extreme mood changes, raising questions about the validity of retrospective questionnaires about BPD and their usefulness for treatment evaluation.…”
mentioning
confidence: 98%
“…That BPD patients suffer from dramatic ups and downs in affect has always been clinical experience, but only recently have empirical studies verified the ups and downs in BPD by tracking affective states over time in daily life Links et al, 2007;. At the same time, research has shown that the relationship between questionnaire trait measures of affective instability and affective instability, as experienced in everyday life, is modest at best (Links, Heisel, & Garland, 2003;Solhan, Trull, Jahng, & Wood, 2009). The study by Solhan et al even showed that BPD patients do not remember their most extreme mood changes, raising questions about the validity of retrospective questionnaires about BPD and their usefulness for treatment evaluation.…”
mentioning
confidence: 98%
“…This technique provides results that are consistent, different and more valid than when patients are asked at a later point to recall their experiences. 36 Several characteristics may help distinguish mood fluctuations in patients with borderline personality disorder from those in healthy controls. Several studies suggest that negative emotions may persist for longer and be more intense in patients with the disorder than in healthy controls, although this is not true for positive emotions.…”
mentioning
confidence: 99%
“…Sumado a ello, los resultados muestran cómo las hipó-tesis funcionales incluían un mayor número de elementos en la descripción de la problemática, en comparación con los motivos de consulta, lo que puede estar relacionado con que éstas son llevadas a cabo con el fin de sintetizar la información recogida durante el proceso de evaluación (Muñoz-Martínez & Novoa-Gómez, 2010), incluyendo elementos que no son mencionados en una primera instancia por el consultante, pero que se hacen evidentes al hacer uso de los diferentes métodos de evaluación (Avendaño, 2001;Solhan, Trull, Jahng & Wood, 2009) y del análisis funcional que se ejecuta tras la exploración de la información desde la perspectiva conductual (Haynes et al, 1997).…”
Section: Discussionunclassified